Social inequalities in social-emotional problems among preschool children: a population-based study in Sweden - Masoud Vaezghasemi; Anni-Maria; Marie Lindkvist; Sven-Arne Silfverdal; Wolfgang Lohr; Anneli Ivarsson (Taylor & Francis Group, 2023)
Background Social-emotional ability is important for overall health and wellbeing in early childhood. Recognizing preschool children in need of extra support, especially those living in unfavourable conditions, can have immediate positive effects on their health and benefit their wellbeing in the long-term. Objectives The aim of this study is to investigate whether there are social inequalities in preschool children's social-emotional problems, and whether inequalities differ between boys and girls. Method This study utilized repeated measures from cross-sectional population-based surveys of three-year old children (2014-2018). The final study population comprised of 9,099 children which was 61% of all the eligible children in Västerbotten County during the study period. The Ages and Stages Questionnaires: Social-Emotional (ASQ:SE) 36-month interval was used to measure children's social-emotional ability. Social inequalities were studied with respect to parents' income, education, and place of birth, for which data was obtained from Statistics Sweden. Multiple logistic and ordered regressions were used. Results Among 3-year-olds, social-emotional problems were more common in the most vulnerable social groups, i.e. parents in the lowest income quintile (OR: 1.45, p < 0.001), parents with education not more than high school (OR: 1.51, p < 0.001), and both parents born outside Sweden (OR: 2.54, p < 0.001). Notably, there was a larger difference in social-emotional problems between the lowest and highest social categories for girls compared to boys. Higher odds of social-emotional problems were associated with boys not living with both parents and girls living in the areas of Skellefteå and Umeå, i.e. more populated geographical areas. Conclusion Already at 3-years of age social-emotional problems were more common in children with parents in the most vulnerable social groups. This does not fulfil the ambition of an equitable start in life for every child and might contribute to reproduction of social inequalities across generations.